2008
DOI: 10.1159/000161877
|View full text |Cite
|
Sign up to set email alerts
|

Transconjunctival 20-Gauge Vitrectomy: A Pilot Study

Abstract: Purpose: To determine the efficacy of a novel technique for a ‘transconjunctival 20-gauge vitrectomy’ (T20V). Methods: In total, 12 eyes of 12 consecutive patients were included in a prospective study. The mean age was 58 years (range: 38–74 years); 4 patients were male and 8 were female. The T20V was indicated when short-duration vitrectomy was envisioned: macular surgery for macular hole and epiretinal membrane therapy, moderate vitreous hemorrhage due to retina vein occlusions or diabetic retinopathy, or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Our series had no cases of postoperative vitreous hemorrhage in either group in comparison with the study reported by Aguni et al, which showed mild vitreous hemorrhage in 25% of cases; however, these all spontaneously cleared up within weeks 14. We also had no cases of vitreous incarceration at the sclerotomy, whereas Aguni et al did have one case of this 14…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our series had no cases of postoperative vitreous hemorrhage in either group in comparison with the study reported by Aguni et al, which showed mild vitreous hemorrhage in 25% of cases; however, these all spontaneously cleared up within weeks 14. We also had no cases of vitreous incarceration at the sclerotomy, whereas Aguni et al did have one case of this 14…”
Section: Discussionsupporting
confidence: 57%
“…Disadvantages of the trocar system include the longer intraoperative time, a slightly higher risk of scleral wound trauma, and the increased cost of the surgery 13,14…”
Section: Discussionmentioning
confidence: 99%
“…The induced astigmatism is usually transient and returns to the baseline level by 1 to 4 months after surgery. The increase in the postoperative astigmatism may be attributed to the scleral cautery and suturing at the entry port 46. Yanyali et al concluded that regular and irregular astigmatism of the cornea did not change when 25-gauge TSV was used 7…”
Section: Introductionmentioning
confidence: 99%
“…Both studies suggested that oblique incisions in a beveled or tunneled fashion provide better wound apposition and stability compared to straight incisions. Oblique scleral incisions promoted also for "transconjunctival 20gauge vitrectomies" a safe approach, 3 while straight or tangential injections may remain open, inducing leakage and ocular hypotony even with 30-gauge needles. 4 Oblique or angled incisions are believed to decrease wound leakage by having an internal lip that presses against the outer lip through the elevated intraocular pressure, helping to close the wound.…”
mentioning
confidence: 99%